ENVOLVING REGULATIONS ON LOCAL HEAD ELECTIONS IN POST-REFORM INDONESIA: SHIFTING FROM ELITE POLITICAL DOMINANCE TO POPULAR SOVEREIGNTY - Firman (Bengkoelen Justice : Jurnal Ilmu Hukum, 2026)
This research examines the evolution of Indonesia's post-reformasi regulations on local head elections, shifting from elite political dominance to popular souvereignty. It scrutinizes the Constitutional Court's (MK) interpretation of “elected democratically” in Article 18 (4) of the 1945 Constitution, alongside the development of rules curbing elite influence. Adopting a normative juridical methodology centered on legislative analysis and MK rulings, the study uncovers interpretive dualism between direct democracy and DPRD mediated representation, especially in special autonomy regions. Nonetheless, the MK, as ultimate constitutional arbiter, has solidified direct democracy via pivotal decisions No. 72-73/PUU-II/2004, 85/PUU-XX/2022, and 135/PUU-XXII/2024 that synchronize regional elections with national polls and eliminate DPRD selection pathways. Regulatory progression originated in elite-centric frameworks like Law No. 22 of 1999 on Regional Administration and Law No. 22 of 2014 on Governor, Regent, and Mayor Elections, advancing to sovereignty-affirming reforms under Law No. 32 of 2004 on Local Government and Law No. 10 of 2016 (second amendment to Law No. 1 of 2015). Direct public elections thus emerge as an indispensable (conditio sine qua non) for realizing popular sovereignty, bolstering local decentralization and democratization.